1997
DOI: 10.1111/j.1432-1033.1997.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Major Detoxication Functions by Phenobarbital and 3‐Methylcholanthrene in Co‐Cultures of Rat Hepatocytes and Liver Epithelial Cells

Abstract: In the present study, we analysed the expression of monooxygenase activities and mRNAs associated with cytochrome P-450 (CUP), including CYPlAU2, CYP2B1/2, CYP2C6, CYP2E1, CYP3A1/2, glutathione transferase a (GSTa), aldehyde dehydrogenase and epoxide hydrolase in co-cultures of primary rat hepatocytes and rat liver epithelial cells. We observed that pentoxyresorufin 0-deethylation activity was well maintained and ethoxyresorufin O-deethylation activity gradually decreased during co-culture time. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…This enhancement effect of 3- methylcholanthrene on glutathione-s-transferase activity is supported by various investigators [22,23]. This finding suggests the role of glutathione-s-transferase in detoxification of polycyclic aromatic hydrocarbons.…”
Section: Discussionsupporting
confidence: 61%
“…This enhancement effect of 3- methylcholanthrene on glutathione-s-transferase activity is supported by various investigators [22,23]. This finding suggests the role of glutathione-s-transferase in detoxification of polycyclic aromatic hydrocarbons.…”
Section: Discussionsupporting
confidence: 61%
“…For that purpose, liver cells cocultures (hepatocytes with non-parenchymal cell [17,18] and hepatocytes with biliary cells [19]) have been developed, and these models have demonstrated that cell-cell interactions preserved hepatocytes, functionality [20]. Even if various studies are done on an artificial 3D matrix [21,22] and in coculture [23,24], the reconstructed physiology does not completely mimic in vivo 3D tissue.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable step forward in long-term maintenance of differentiated hepatocytes was made by adding another liver epithelial cell type (126). When cocultured with rat liver epithelial cells probably derived from primitive biliary cells, hepatocytes from various species including humans survive for several weeks and retain various liverspecific functions; these include production of plasma proteins, expression of both phase I and phase II drug metabolizing enzymes, and taurocholate uptake (52,71,(127)(128)(129)(130)(131)(132)(133)(134)(135) (71,126,128) and with preservation of communication through gap junctions (136). These two features could be related because in pure hepatocyte cultures the addition of proteoglycans improves gap junction activity (137).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 99%